Management of epilepsy in pregnancy in eastern China: A survey from the Zhejiang association against epilepsy - Xu, Zheng-Yan-Ran; Qian, Ping; Cai, Meng-Ting; Ding, Mei-ping; Guo, Yi (Frontiers in Neurology, 2022)
Objective We aimed to evaluate the knowledge of the board members of the Zhejiang Association Against Epilepsy (ZAAE) regarding pregnancy of women with epilepsy (WWE), as well as their clinical practice and obstacles in the management of WWE. Methods A cross-sectional survey was conducted among the board members of the ZAAE using a questionnaire based on the management guidelines for WWE during pregnancy in China. We recorded the demographic characteristics of the surveyed practitioners, the coincidence rate of each question, clinical practice, and the barriers encountered in managing WWE. Results This survey showed that the average knowledge score of the surveyed practitioners was 71.02%, and the knowledge score of neurologists was higher than that of neurosurgeons. Knowledge regarding the following three aspects was relatively poor: whether WWE is associated with an increased risk of cesarean section and preterm delivery, the preferred analgesic drugs for WWE during delivery, and the time of postpartum blood concentration monitoring. After multiple linear regression analysis, the score of neurologists was correlated to the number of pregnant WWE treated each year. In addition, the biggest difficulty in the management of WWE during pregnancy is the lack of patient education and doctors training on pregnant epilepsy management. Conclusion Our study revealed the ZAAE board members' knowledge and management status of pregnant WWE. In addition, our study identified the biggest obstacle to the management of WWE during pregnancy, and emphasized the importance of training and practice of epilepsy knowledge during pregnancy for practitioners and the significance of interdisciplinary communication.